Assessment and predictability of ANB angle - Chandra Pavan Kumar; Godfrey Keith (Sciendo, 1990)
This cephalometric study consisting of thirty three orthodontic patients in the age group of 13 to 15 years was carried out to: 1. Evaluate the relationship between angle ANB and horizontal distance between jaws at the level of point A (r = 0-99); 2. Evaluate the relationship between angle ANB and Wits appraisal (r = 0 95 when mandibular plane angle is within normal limits of 32±5); 3. Predict angle ANB from Wits appraisal and vice versa (which was 90 percent correct in mesofacial type and obtained by the regression equation: angle ANB = 2 31 +1-00 x Wits value; and 4. Evaluate the validity of angle ANB compared to other methods (angle ANB 785 percent in agreement with the standard followed by Wits 64-28 percent).